1975
DOI: 10.2135/cropsci1975.0011183x001500030041x
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of Nitrate Reductase and Cyanide Levels in Seedlings of Grain Sorghum Cultivars1

Abstract: Seedlings of 41 cultivars of grain sorghum [Sorghum bicolor (L.) Moench] including 30 hybrids and all but two of their parents were grown in a growth chamber; harvested 10, 14, and 18 days after planting; and assayed for hydrolizable cyanide and in vitro and in vivo nitrate reductase activity (NRA). The genotype X age variance component was essentially equal to the genetic variance for each character, which suggest that genotype X environment interactions are major components of the phenotypic variance. Cyanid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1977
1977
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Krauss (14), in a study not included in Nass's review, concluded that HCN-p was conditioned by four genes with additive effects without dominance. Other studies conducted since Nass's review reported different conclusions on the importance of additive and nonadditive effects (2,4,9). Recently, Gorz et al (10) found that seedlings of sorghum lines KS8 and N32 were high in HCN-p, but the HCN-p of flag leaves from field-grown plants of KS8 was only about 1/10 as high as that of N32 flag leaves.…”
mentioning
confidence: 99%
“…Krauss (14), in a study not included in Nass's review, concluded that HCN-p was conditioned by four genes with additive effects without dominance. Other studies conducted since Nass's review reported different conclusions on the importance of additive and nonadditive effects (2,4,9). Recently, Gorz et al (10) found that seedlings of sorghum lines KS8 and N32 were high in HCN-p, but the HCN-p of flag leaves from field-grown plants of KS8 was only about 1/10 as high as that of N32 flag leaves.…”
mentioning
confidence: 99%
“…More recent studies of T repens have revealed that there are different functional alleles coding for the cyanogenic glycoside that result in the production of different amounts of the chemical (Hughes et al, 1984). Tn S. bicolor, cyanogenesis appears to be a polygenic trait (Nass, 1972;Eck et a!., 1975). Polymorphism for cyanogenesis has also been reported in natural populations of the bracken fern, Pteridium aquilinum (Cooper-Driver & Swain, 1976).…”
Section: *Correspondencementioning
confidence: 99%
“…Polymorphic populations, having cyanogenic as well as acyanogenic individuals, have been reported for some forage, crops and wild plants (Grant & Sidhu, 1967; Nass, 1972; Eck et al ., 1975; Hughes, 1991). In these populations acyanogenesis was attributed to the lack of β‐glycosidase but not of the cyanogenic glycosides (Kakes, 1990).…”
Section: Introductionmentioning
confidence: 99%